2019
DOI: 10.1111/asj.13188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calving difficulty on dry matter intake immediately after calving of dairy cows

Abstract: We investigated the influence of calving difficulty on dry matter intake (DMI) in Holstein cows immediately after calving using 15 pregnant heifers and 15 multiparous cows. DMI was measured for 6 days after calving. Calving difficulty was evaluated with a calving score, and urinary cortisol was measured. The calving score was higher in the first lactation heifers than in the multiparous cows. The average DMI 6 days after calving was lower in the first lactation heifers than in the multiparous cows. The urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The average DMI during the first week after calving was positively associated with the serum Ca concentration immediately after calving ( p < .01). This result agreed with those obtained by Wynn et al () and Reshalaitihan and Hanada (). Wynn et al () demonstrated that serum Ca concentration during the first week after calving was positively associated with the rumen contraction frequency and the DMI after calving.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The average DMI during the first week after calving was positively associated with the serum Ca concentration immediately after calving ( p < .01). This result agreed with those obtained by Wynn et al () and Reshalaitihan and Hanada (). Wynn et al () demonstrated that serum Ca concentration during the first week after calving was positively associated with the rumen contraction frequency and the DMI after calving.…”
Section: Discussionsupporting
confidence: 94%
“…A higher incidence of calving difficulty in first‐lactation heifers than in multiparous cows has already been reported (Berry, Lee, MacDonald, & Roche, ; Civelek, Celik, Avci, & Cingi, ). Reshalaitihan and Hanada () reported that the average DMI 6 days after calving was negatively associated with the calving score and urinary cortisol concentration at 4 days after calving and that the calving score and the urinary cortisol concentration were higher in first‐lactation heifers than in multiparous cows. It has also been reported that the DMI after calving was lower in cows with dystocia than in cows that calved normally (Bareille et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mammi et al (2021) identified that problematic calving is associated with reduced rumination and rest time for cows. The negative impact of heavy calving on the feed dry matter intake was also identified (Reshalaitihan & Hanada, 2019). A study by Antanaitis et al (2021) showed that heavy calving causes a decrease in the concentration of lactose in milk and increases the risk of mastitis.…”
Section: Introductionmentioning
confidence: 95%